Reinstatement of Desmos subbiglandulosus (Annonaceae) in Borneo - Isna Arofatun Nikmah; Tatik Chikmawati; Rugayah Rugayah (Floribunda, 2019)
Desmos subbiglandulosus (Miq.) Merr., previously placed as a synonym of Desmos dumosus (Roxb.) Saff., is reinstated based on the examination of herbarium specimens and type material of D. subbiglandulosus from Borneo deposited in Herbarium Bogoriense. The specimens of D. subbiglandulosus and D. dumosus are morphologically distinct. All the specimens Desmos from Borneo previously identified as D. dumosus should belong to D. subbiglandulosus.